2009
DOI: 10.1007/978-3-642-04277-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Mining Rules for the Automatic Selection Process of Clustering Methods Applied to Cancer Gene Expression Data

Abstract: Abstract. Different algorithms have been proposed in the literature to cluster gene expression data, however there is no single algorithm that can be considered the best one independently on the data. In this work, we applied the concepts of Meta-Learning to relate features of gene expression data sets to the performance of clustering algorithms. In our context, each meta-example represents descriptive features of a gene expression data set and a label indicating the best clustering algorithm when applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…In recent years, Meta-Learning has been extrapolated to other domains of application, such as in the selection of time series forecasting models [18], design of planning systems [25], combinatorial optimization [26], software engineering [27] and bioinformatics [9,28,29]. In such domains, Meta-Learning can be seen as tool for analysis of experiments performed by using a number of algorithms on a large set of problems that can be solved by these algorithms.…”
Section: Meta-learningmentioning
confidence: 99%
“…In recent years, Meta-Learning has been extrapolated to other domains of application, such as in the selection of time series forecasting models [18], design of planning systems [25], combinatorial optimization [26], software engineering [27] and bioinformatics [9,28,29]. In such domains, Meta-Learning can be seen as tool for analysis of experiments performed by using a number of algorithms on a large set of problems that can be solved by these algorithms.…”
Section: Meta-learningmentioning
confidence: 99%
“…Even though this is a common approach for selection/ranking of supervised learning algorithms [20], in the area of clustering this is a relatively new and unexplored topic [21]. Still, preliminary results in the area of microarray data clustering [21], [22] are promising. These studies explicitly concluded that clustering meta-learning frameworks would benefit from including a larger number of algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, concepts and techniques of meta-learning have been applied in various application domains, such as selection of models of temporal series prediction [9], software engineering [16] and bioinformatics [17], [18], [19], [10]. In the literature, there are different interpretations (definition) of the term meta-learning, as in [8], [20], [21].…”
Section: Meta-learningmentioning
confidence: 99%